(untitled) (Research, Society and Development, 2020)
The oil of the coconut dry fruit (Cocos nucifera L.) has a vegetable origin extracted from the coconut tree, belonging to the Arecaceae family and the subfamily Cocoideae. It has great potential for industrial use as it has applications in several productive areas. The constant search for products that can add value and bring benefits to humanity has led to the growth in the use of coconut oil in industrial processes, as it is an oil considered stable due to its high level of saturation compared to other edible oils. The objective of this research was to evaluate the oleochemical characteristics of coconut oil from cold extraction processes and industrialized oils, verifying the analysis of the parameters indicative of the quality of these oils, which were as follows: acidity, peroxide, iodine indexes and percentages of free fatty acids. A comparative analysis of commercial coconut oil and coconut oil adapted by the Bligh & Dyer method was performed. The samples in both treatments were obtained from local stores and were analyzed in triplicates. The analyzed parameters were similar for both treated oils, it was within the standards required by the RDC legislation No. 270 and CODEX alimentarius, indicating good quality for consumption. Only the data for the iodine index in both treatments were high, and may have been influenced by the seasonality of the fruit, by the extraction method or by industrial processes.